Mechanical Properties and Strain Hardening Behaviour of Magnesium Alloys and Composites - Lukac, Pavel; Trojanova, Zuzanka (Communications - Scientific letters of the University of Zilina, 2010)
Selected magnesium alloys and composites with magnesium alloy matrix were deformed at temperatures between room temperature and 300 °C at constant strain rate. The testing temperature influences significantly the deformation behaviour of the al/loys. The flow stress decreases with increasing temperature. The work hardening rate decreases with stress (strain) and temperature. Above about 200 °C, a dynamic balance between hardening and softening is observed. Stress relaxation tests were performed to identify thermally activated dislocation motion. The main thermally activated process is very probably the glide of dislocation in non-basal planes. The internal component of the applied stress decreases significantly with increasing temperature.